2018
DOI: 10.3892/mmr.2018.9072
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CUEDC2 prevents doxorubicin‑induced cardiotoxicity in H9c2 cells

Abstract: Treatment with doxorubicin (DOX), which is an effective anticancer agent, is limited by cardiotoxicity. CUE domain-containing 2 (CUEDC2) serves a role in numerous cellular processes. The present study aimed to elucidate the potential function of CUEDC2 in DOX-induced cardiotoxicity. Cell Counting kit-8 assay demonstrated that DOX induced cytotoxicity of H9c2 cells in a dose-dependent manner. Flow cytometry demonstrated that downregulation of CUEDC2 reduced the levels of DOX-induced reactive oxygen species. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Our results are consistent with a study by Zhang et al showing that Dox induced cell damage in a dose-and time-dependent manner. Dox (5 μM) caused about 30% reduction in H9c2 cell viability after incubation for 24 h [20], which is similar to our data. By contrast, Dallons et al showed Dox (1-50 μM) had no effect on cell viability after incubation for 4 h, whereas Dox (1 μM) showed 60% reduction in cell viability after 24 h treatment when cell viability was measured by crystal violet assay [21].…”
Section: Dox Induced H9c2 Cell Damage By Increasing Intracellular and Mitochondrial Rossupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are consistent with a study by Zhang et al showing that Dox induced cell damage in a dose-and time-dependent manner. Dox (5 μM) caused about 30% reduction in H9c2 cell viability after incubation for 24 h [20], which is similar to our data. By contrast, Dallons et al showed Dox (1-50 μM) had no effect on cell viability after incubation for 4 h, whereas Dox (1 μM) showed 60% reduction in cell viability after 24 h treatment when cell viability was measured by crystal violet assay [21].…”
Section: Dox Induced H9c2 Cell Damage By Increasing Intracellular and Mitochondrial Rossupporting
confidence: 91%
“…Dox is a powerful chemotherapeutic drug and widely used in solid cancer treatment [19]. Dox usage is limited due to induction of irreversible cardiotoxicity [1,20]. This damage is characterized by cardiac cell apoptosis or necrosis which can lead to cardiomyopathy [21].…”
Section: Dox Induced H9c2 Cell Damage By Increasing Intracellular and Mitochondrial Rosmentioning
confidence: 99%
See 1 more Smart Citation
“…Foxo signaling is important for the regulation of cardiomyocyte development and survival. Doxorubicin has been shown to induce cardiomyocyte apoptosis and atrophy through CDK2-mediated activation of FOXO1 signaling [ 43 ], while overexpression of Foxo3A attenuates AIC by inhibiting MIEF2 and mitochondrial disintegration in cardiomyocytes [ 44 ], and activation of FOXO3A signaling reduces anthracycline-induced apoptosis in rat cardiomyocytes [ 45 ], indicating the diversity of FOXO signal in cardiomyocytes. In addition, PI3K-AKT activation was found to upregulate FOXO3A signaling to antagonize AIC [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lipid peroxidation was evaluated by the Stuart et al method by estimating the malondialdehyde (MDA) levels . Nitric oxide (NO) level was assessed by the Singh et al method …”
Section: Methodsmentioning
confidence: 99%